An Appreciation of the First Movement of Mozart’s Piano Sonata in D Major, KV.576 - Wang Le (SHS Web of Conferences, 2024)
The most outstanding and influential composer of the Viennese classical school is Mozart, and the Piano Sonata in D Major (KV.576) is Mozart's last sonata, written in 1789. This paper will mainly focus on the first movement of KV.576, analysing it in detail from the compositional background, the period background, the performance technique, and the perception of the performance. KV.576 achieves balance and harmony by contrasting composition, theme, and texture. Instead of following the traditional style, Mozart's music reinterprets the new music with the vocabulary of the time to realize the aesthetic ideal of classical music.